RANCANGAN WEBSITE SMA NEGERI 7 BATANGHARI - Ahmad Louis; Bobi Hartanto (JURNAL AKADEMIKA)
SMA 7 Batanghari is a school in the provision of information are still using manual systems, where information could be generated manually, which is news to the public information obtained from a brochure or from one person to another. As for the design of information systems is to use Macromedia Dreamweaver 8 application and PHP, which will with this information system can support and provide services need information, help facilitate the conduct repairs if something goes wrong in an information and data, the data helps in finding information about help leaders to make decisions that are useful in making decisions that are useful in determining step further discretion.